IMPLEMENTASI ALGORITMA C4.5 UNTUK PENENTUAN PENERIMAN BEASISWA (Studi Kasus: SMA N 2 Cepu) - retno wahyusari (SIMETRIS, 2021)
One of human rights is the right to education. In organizing quality education requires substantial costs. Scholarships are a way to overcome cost problems for those who are less well off. Scholarships are assistance from the government of the private sector in the form of a sum of money given to students who are currently or who will attend school education. The granting of this sholarships is very important, in order to give students peace of mind in attending teaching and learning. Because many students apply for scholarships and too many indicators result in receivi9ng scholarships that are not well targeted. To overcome this problem, a scholarships acceptance Decision Support System was created using the C4.5 Algorithm which will make it easier for the 2 Cepu High School selection team to select students who are entitled to scholarships because in High School 2 Cepu the selection proses still uses manual methods and requires a long time. C4.5 Algorithm is a development of the ID3 Algorithm based on Supervised Learning. By using the Decision Tree method C4.5 Algorithm it is hoped that the awarding of scholarships can be right on target. In this study the researchers used class 11 and class 12 as training data to determine the decision tree in RapidMiner, while class 10 data became the testing data for the matlab proses. There are 99 students in grades 11 and 12 who are eligible for scholarships, while 402 grade 11 and 12 students who do not deseve a scholarship. The results of the decision tree support system research with the decision tree method for the recommendation of students to be eligibel or not to receive sholarships using the C4.5 arlgorithm can prosuce a high level of accuracy that is equal to 96,80%.